Histone Post-translational Modifications in Huntington’s and Parkinson’s Diseases - Emiliano Pena-Altamira, Luis; Polazzi, Elisabetta; Monti, Barbara (Current Pharmaceutical Design, 2013)
Gene expression is controlled by several epigenetic mechanisms involving post-translational modification of histones (acetylation, phosphorylation and others). These mechanisms in the brain are not only important for normal function but also for the development of pathologies when their derangement does occur. The present review deals with post-translational modifications of histones in two neurodegenerative diseases characterized by different etiology and pathological progression, Huntington’s disease and Parkinson’s disease. A relatively large body of evidence supports an important role of these mechanisms in Huntington’s disease while knowledge of similar mechanisms in Parkinson’s disease is at a lower degree of understanding. Starting from available information on pathologies, the present state of possible therapeutic targets is considered and future developments are discussed.
Keywords: HDACs inhibitors